A review of the genus Stratiomys Geoffroy (Diptera: Stratiomyidae) from India with description of a new species - Yatoo, Suhaib Firdous; Maqbool, Amir; Wachkoo, Aijaz Ahmad (European Journal of Taxonomy, 2023)
A review of the genus Stratiomys from India is presented. The new species Stratiomys brunettii sp. nov. is described based on male and female specimens collected from the Kashmir Himalayas. The only other congener previously recorded in India, Stratiomys approximata, is redescribed. A key to the species is presented.